THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY, FRIENDS, ENVIRONMENT, AND ADVERTISING WITH THE EATING PATTERNS OF FKM STUDENTS AT MUHAMMADIYAH UNIVERSITY OF ACEH - Khairunnisa, Khairunnisa; Aramico, Basri; Amin, Fauzi Ali (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: Diarrhea is a significant public health problem in many countries, including Indonesia. Meunasah Balee Village in the Lhoknga Subdistrict has been identified as the area with the highest number of diarrhea cases reported at the local Community Health Center (Puskesmas) in 2017. This study aims to examine the relationship between the physical condition of dug wells and the incidence of diarrhea in Meunasah Balee Village. Method: This study employed a descriptive-analytic method with a cross-sectional design. The study population consisted of all households (81 households) that had dug wells. Data collection was conducted over 10 days from January to February 2019 through physical measurements, interviews, and observations. Data were analyzed using the Chi-square test with the help of SPSS version 20. Result: The study found a significant relationship between several physical factors of dug wells and the incidence of diarrhea. The distance between septic tanks and dug wells was significantly associated with diarrhea incidence (p value = 0.004), as was the distance from pollution sources (p value = 0.002), and the physical condition of the wells (p value = 0.018). Laboratory examination results showed that all samples from households with diarrhea cases (100%) failed to meet microbiological quality standards based on the Most Probable Number (MPN) test. Recommendation: The study concludes that the physical condition of dug wells—such as the distance to septic tanks, distance to pollution sources, and the overall condition of the well—is directly associated with the incidence of diarrhea in Meunasah Balee Village. It is recommended that the Health Office conduct intensive education campaigns on the importance of clean water supply, septic tank management, and pollution control as preventive measures to reduce diarrhea cases in the area.